Deciphering the tubulin code: roles and mechanisms of microtubule post-translational modifications in gastrointestinal tumors: a narrative review - Zhou, Chaofeng; Li, Dongxiao; Wang, Zipeng; Xie, Meng; Ding, Xiangming; Li, Deyu (Journal of Gastrointestinal Oncology, 2026)
Background and Objective: Microtubules (MTs) are essential components of the cytoskeleton and regulate fundamental cellular processes, including cell division, maintenance of cell shape, and intracellular transport. Post-translational modifications (PTMs) of tubulin, such as acetylation, detyrosination, methylation, and polyglutamylation, diversify microtubule functions and constitute the “tubulin code”. Increasing evidence suggests that dysregulated microtubule PTMs contribute to tumor progression. This review summarizes the clinical relevance, molecular mechanisms, and therapeutic potential of microtubule PTMs in gastrointestinal tumors.Methods: A narrative review was conducted using PubMed, EMBASE, Web of Science, and Google Scholar to identify relevant studies on microtubule PTMs in gastrointestinal tumors. Search terms included “microtubule”, “tubulin”, “post-translational modification”, “acetylation”, “detyrosination”, “tyrosination”, “polyglutamylation”, “polyglycylation”, “methylation”, and “phosphorylation”, together with terms related to gastrointestinal malignancies. Reference lists of relevant articles were also screened. Peer-reviewed original studies, relevant reviews, and representative translational reports were narratively synthesized according to clinical associations, molecular mechanisms, regulatory enzymes, and therapeutic implications.Key Content and Findings: Current evidence indicates that microtubule PTMs are closely involved in the progression of gastrointestinal tumors. Acetylation, detyrosination, methylation, and polyglutamylation regulate microtubule stability, intracellular transport, mitosis, migration, invasion, angiogenesis, mechanotransduction, and tumor microenvironment remodeling. Key regulatory enzymes, including HDAC6, αTAT1, TTL, TTLLs, and VASH1/2, have emerged as potential biomarkers and therapeutic targets in gastrointestinal malignancies.Conclusions: Microtubule PTMs represent an important regulatory layer in gastrointestinal tumor biology and may provide new opportunities for biomarker development and targeted therapy. However, their clinical application remains limited by insufficient tumor-specific validation and incomplete understanding of PTM crosstalk. Further studies integrating mechanistic investigation, large clinical cohorts, and multi-omics approaches are needed to promote translation of the tubulin code into precision oncology.